Natureza jurídica do mandado monitório - Vicente de Paula Marques Filho (Scientia Iuris, 1999)
The study of the monitory procedure and the verification of the juridical nature of the injuctive court order, introduced in the Civil Suit Proceeding by the Law n° 9.079/95 from July 14, 1995, are the purposes of this work. As for the specific purpose of the work the conclusion in that the monitory court order, promulgated at first time, has juridical nature of a convictional veredict suspensively conditioned to the non opposition of embargoes, with competence for declaring the existence or inexistence of the controverted material juridical relation. The conclusions of the work are legitimate in face of the constitutional garantee of the due process of law, due to the broad possibility as reaction and defense garanted to the convict. O trabalho tem por finalidade a verificação da natureza jurídica do mandado injuncional, introduzido no Código de Processo Civil pela Lei n° 9.079/95, de 14 de julho de 1995. Para tanto, são analisadas as diversas opiniões da doutrina nacional e estrangeira. As conclusões são no sentido de que o mandado monitório, expedido liminarmente, tem natureza jurídica de uma sentença condenatória suspensivamente condicionada, com aptidão para declarar a existência ou inexistência da relação jurídica material controvertida. As conclusões são legítimas em face da garantia constitucional do contraditório, devido à ampla possibilidade de reação e defesa franqueados ao réu.